Validity and reliability of the Arabic version of the revised illness perception questionnaire for patients with hypertension - Al-Ghamdi, Sameer; Al Muaddi, Alhaytham Mohammed; Alqahtani, Nawaf Ali; Alhasoon, Tamim Yahya; Basalem, Abdulaziz Abdullah; Altamimi, Abdulrahman Abdullah (Frontiers in Public Health, 2022)
Background: Hypertension is one of the leading causes of morbidity and mortality in Saudi Arabia affecting 31.4% of the population. The Illness Perception Questionnaire-Revised (IPQ-R) is a validated and reliable tool for assessing the perception of hypertension among patients. This cross-sectional study aimed to translate the Revised Illness Perception Questionnaire (IPQ-R) into Arabic and validate it among Arabic patients with hypertension from the outpatient departments of the Prince Sattam University Hospital and King Khalid Hospital (KKH) in Al-Kharj City in the Kingdom of Saudi Arabia. Methods: A bilingual panel of doctors and medical translators was assembled to translate the IPQ-R into Arabic. The questionnaire was administered to 100 adult Arabic speaking patients with clinically diagnosed primary hypertension. Patients with secondary hypertension or complications of hypertension were excluded from the study. Results: Fifty-seven patients (57%) were male and sixty-five (65%) were older than 40 years. Headache was the most common symptom of hypertension reported by 65% of the participants. The internal consistency of the questionnaire excluding the domain of ‘Disease Identity’ was 0.76 indicating satisfactory consistency. There were weak to moderate positive linear correlations (r = 0.003 – 0.561) between the domains of IPQ – R suggesting a reasonable discriminant validity among the domains. Conclusion: The Arabic version of the IPQ-R for hypertensive patients is a consistent, valid, and reliable tool to be used by researchers or clinicians for assessing knowledge, beliefs, and attitudes of Arabic speaking patients with hypertension living in Saudi Arabia.